The destruction of chlorinated hydrocarbons by means of reductive pyrolysis - Van der Westhuizen, E.(Elenora) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.